Pengaruh Profitabilitas, Ukuran Perusahaan, Debt To Equity Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan (Studi Pada Perusahaan Asuransi yang Terdaftar di BEI) - Riswan RISWAN; Tri Lestari Saputri (Jurnal Akuntansi dan Keuangan, 2015)
This study aims to analyze the factors that affect the timeliness of financial reporting ininsurance companies listed in Indonesia Stock Exchange. The factors examined in this study are profitability, firm size, and debt to equity as the independent variable while punctuality as the dependent variable. Based on the problems and research objectives, this study uses quantitative research. The data used in this study are secondary data from financial statements and selection of samples by using judgment sampling / purposive sampling. The results of this study revealed no significant influence of profitability, firm size, debt to equity to the timeliness of the financial statements of the insurance companies listed on the Indonesia Stock Exchange in the financial reporting data in 2010 to 2012.